Cover Image. (25th July 2019) - Fan, Bo; Li, Yunfei; Bi, Yong; Tong, Ling; Li, Dongxiang; Wang, Yi
Abstract : The back cover image is based on the Special Issue Article Design of multi‐drug combinations for poly‐pharmacological effects using composition‐activity relationship modeling and multi‐objective optimization approach: Application in traditional Chinese medicine by Bo Fan et al., https://doi.org/10.1111/cbdd.13396 . Cover image design © Bo Fan.